Development of anti-biofouling feed spacers to improve performance of reverse osmosis modules. (15th November 2018) - Rice, Douglas; Barrios, Ana C.; Xiao, Zhiwei; Bogler, Anne; Bar-Zeev, Edo; Perreault, Francois
Abstract: This study investigates the biofouling resistance of modified reverse osmosis (RO) feed spacers. Control spacers (made of polypropylene) were functionalized with a biocidal coating (silver), hydrophilic (SiO2 nanoparticles) or superhydrophobic (TMPSi-TiO2 nanoparticles) anti-adhesive coatings, or a hybrid hydrophilic-biocidal coating (graphene oxide). Performance was measured by adhesion assays, viability tests, and permeate flow decline in a bench scale RO system. The control spacers proved to be one of the better performing materials based on bacterial deposition and dynamic RO fouling experiments. The good anti-adhesive properties of the control can be explained by its near ideal surface free energy (SFE). The only surface modification that significantly reduced biofouling compared to the control was the biocidal silver coating, which outperformed the other spacers by all measured indicators. Therefore, future efforts to improve spacer materials for biofouling control should focus on engineering biocidal coatings, rather than anti-adhesive ones. Graphical abstract: Image 1 Highlights: Control spacers exhibit strong anti-adhesive characteristics. Surface free energy highly influences whether a material is anti-adhesive. Biocidal coatings are a promising way to improve feed spacer performance.